Hernia Mesh: Understanding the Properties and Selection of Materials for Hernia Repair - Techapongsatorn, Suphakarn (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Hernia repair remains one of the most common procedures in general surgery, and mesh reinforcement has become the standard of care to reduce recurrence rates. A wide variety of mesh types and materials have been developed to address specific surgical needs and patient risk factors. This review provides an updated overview of synthetic and biological meshes, highlighting their properties, advantages, and limitations. Non-absorbable synthetic meshes, such as polypropylene and polyester, offer durable strength but may induce significant inflammatory responses, while ePTFE minimises adhesions at the cost of poor tissue integration. Absorbable synthetic meshes provide temporary support in contaminated fields but risk early degradation. Biological meshes derived from human or animal tissue offer high biocompatibility and suitability for infected settings but are expensive and mechanically weaker. Composite meshes combine different materials to balance tissue integration with anti-adhesive barriers for safe intraperitoneal use. Key factors in mesh selection include placement location (extra- vs intra-peritoneal), wound condition (clean vs contaminated), desired properties (lightweight, macroporous, monofilament structure), and appropriate sizing with sufficient overlap to prevent recurrence. Understanding these considerations is essential for optimising patient outcomes, reducing complications such as chronic pain or infection, and ensuring long-term hernia repair durability.